2021
DOI: 10.3390/jcm10214939
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in the Expression Regulation of Dopamine-Related Genes and Proteins in Endometrial Cancer

Abstract: Disruption of the dopaminergic system leads to many diseases, including cancer. Dopamine and its receptors are involved in the regulation of proliferation, cell death, invasion, and migration. Better understanding of the mechanisms involved in these processes could reveal new molecular markers and therapeutic targets. The aim of this study was to determine the expression profile of dopamine-related genes and proteins in endometrial cancer and to assess whether miRNAs are involved in its regulation. Sixty women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…MiR-217 activates the dopamine D2 receptor to protect fibrosis in human renal proximal tubule cells [ 22 ]. One study suggested that miRNA targets the dopamine receptor involved in progression of endometrial cancer [ 23 ]. In contrast to mammals, few studies were conducted on dopamine receptors in insects.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-217 activates the dopamine D2 receptor to protect fibrosis in human renal proximal tubule cells [ 22 ]. One study suggested that miRNA targets the dopamine receptor involved in progression of endometrial cancer [ 23 ]. In contrast to mammals, few studies were conducted on dopamine receptors in insects.…”
Section: Introductionmentioning
confidence: 99%